MENGOPTIMALKAN PEMBELAJARAN AKUNTANSI DASAR MELALUI PEMBUATAN VIDEO EDUKATIF - Bonal, Emilie Monique; Wijoyo, Amin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
This activity aims to improve accounting education by introducing a video-based learning approach that emphasizes understanding the basics of accounting, specifically through the book